First-principle calculations to investigate the elastic and thermodynamic properties of RBRh 3 (R =Sc, y and La) perovskite compounds - Litimein, F.; Khenata, R.; Bouhemadou, Abdelmadjid; Yarub, Al-Douri, Prof. Dr.; S., Omran (Taylor and Francis Group, 2013)
Link to publisher's homepage at http://www.tandfonline.com/